2022
DOI: 10.1590/1414-431x2022e11832
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics analysis reveals universal signatures of the intestinal microbiota in colorectal cancer, regardless of regional differences

Abstract: The human gut microbiota is a complex and dynamic community of microorganisms living in our intestines and has emerged as an important factor for colorectal adenocarcinoma (CRC). The purpose of our study was to investigate the microbiota composition in Brazilian CRC patients compared with a local control population (CTL) to find out which changes could be considered universal or regional features in CRC microbiota. Fecal samples were obtained from 28 CRC and 23 CTL individuals. The 16S rRNA gene was used for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Although Bacteroides fragilis has been previously associated to CRC, 20,95,96 the presence of other species of the genus have been previously reported. 97 Our network show three small clusters of Bacteroides: Bacteroides uniformis and Bacteroides ovatus clusters are both present in both conditions, supporting reports of the genus being common in the human gut, but Bacteroides zhangwenhongi present only in CRC. We could hypothesise that, with the genus being associated to the immune response, the abundance of these species in CRC patients could be related to an immune response of the host, but further studies are required.…”
Section: Discussionsupporting
confidence: 85%
“…Although Bacteroides fragilis has been previously associated to CRC, 20,95,96 the presence of other species of the genus have been previously reported. 97 Our network show three small clusters of Bacteroides: Bacteroides uniformis and Bacteroides ovatus clusters are both present in both conditions, supporting reports of the genus being common in the human gut, but Bacteroides zhangwenhongi present only in CRC. We could hypothesise that, with the genus being associated to the immune response, the abundance of these species in CRC patients could be related to an immune response of the host, but further studies are required.…”
Section: Discussionsupporting
confidence: 85%
“…The phylum Verrucomicrobia includes only one representative species, namely Akkermansia muciniphila , which is abundant in the gastrointestinal tract, and has attracted considerable interest in studies involving microbiota and IBD [ 38 , 39 , 40 ]. In the Fusobacteria phylum, a gram-negative anaerobic bacillus ( Fusobacterium nucleatum ) has a symbiotic relationship with its host but could also cause opportunistic infections and has recently garnered attention in several studies on the role of the microbiome in colorectal cancer [ 41 , 42 ]. The phylum Actinobacteria includes Collinsella and Bifidobacterium , while the common phylum Proteobacteria includes Escherichia and Desulfovibrio genera.…”
Section: Intestinal Microbiota and Inflammatory Bowel Diseasementioning
confidence: 99%
“…Faecal and metagenomic studies by different scientists [92] , [93] indicated that some gut bacterial species are predominant in the faecal samples as well as tumor microenvironments of patients with CRC, in high abundance, compared to those of healthy individuals and normal tissues adjacent to tumor microenvironments. This provides insights into the possible correlation between these bacterial species and colorectal carcinogenesis.…”
Section: Diet-mediated Changes In the Gut Microbial Communitymentioning
confidence: 99%